Performance of three-dimensional reinforced concrete beam-column substructures under loss of a corner column scenario - Kai, Qian (2012)
The vulnerability of conventional reinforced concrete (RC) structures to structural failure due to the loss of corner columns has been emphasized over the past years. However, the lack of experimental tests has led to a gap in the knowledge for the design of RC building structures to mitigate the likelihood of progressive collapse caused by losing a ground corner column. Seven one-third scale RC beam-column substructures were tested to investigate their performance. The variables selected for the test specimens included: beam transverse reinforcement ratios, type of design detailing (non-seismic or seismic) and beam span aspect ratios. Shear failure was observed to have occurred in the corner joint and a plastic hinge was formed at the beam end near to the fixed support in the non-seismic detailed specimens. However, plastic hinges were also formed in the beam end near to the corner joint for the seismically detailed specimen. Vierendeel action was identified as the major load redistribution mechanism before severe failure occurred in the corner joint but a cantilever beam redistribution mechanism dominated after corner joint suffered severe damage. The test results were compared with the DoD design guidelines to highlight the deficiencies of the recently updated guidelines.